Malignant Melanoma Metastasizes to Colonic Polyp - Azharuddin, Muhammad (Cureus, 2018)
Malignant tumors metastasizing to the colon has been observed rarely. Gastrointestinal metastasis can present as benign, unpigmented polyps endoscopically. Most patients do not display any symptoms, and if symptomatic, they usually present with gastrointestinal bleeding. For patients with the history of melanoma, histopathology of polyp can change or alter the course of management. This is a case of a 74-year-old male diagnosed with recurrent melanoma of left ear. Colon cancer screening found blood in his stool. Colonoscopy displayed to have three polyps, one polyp was found to be malignant melanoma. The patient was started on Pembrolizumab, and was tolerating immunotherapy well with no new complaints three months later.